MIRERC 050/2025: ASSESSMENT OF THE RELATIONSHIP BETWEEN SANITATION PRACTICES AND QUALITY OF DRINKING WATER IN RURAL HOUSEHOLDS OF KAJIADO WEST SUB-COUNTY, KENYA - NJOROGE, BERNADETT; Dr. Cynthia Mugo; Dr. Vitalis Too, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
The current research seeks to assess the influence of sanitation practices on bacteriological water quality for drinking in rural households in Kajiado West Sub-County, Kenya. Kajiado County is marked by its semi-arid nature and low levels of improved sanitation, with primary issues of waterborne diseases like diarrhea, typhoid, and cholera, which are likely to be blamed on poor sanitation and contaminated drinking water. The general objective of the study is to analyze how sanitation practices, more precisely waste disposal, handwashing, and water storage vessel handling, influence drinking water quality in this region. Specifically, the research will analyze both bacteriological and physical indicators of water quality, including total coliform levels, E. coli, turbidity and pH, at the point of collection and in household storage containers. The research will utilize a cross-sectional survey design, and the sample size will be 100 households, which will be chosen randomly throughout Kajiado West Sub-County. Data will be collected through structured household surveys. Sampled water will be sent to the lab for microbiological analysis. Statistical analyses will be conducted using R software, to identify significant differences in water quality parameters based on sanitation practices. The research is expected to yield critical insights into the impact of sanitation practices on drinking water quality and provide evidence-based recommendations for improving water safety and public health interventions in rural communities. Findings from this study will contribute to the achievement of the Sustainable Development Goal (SDG) 6, aiming to ensure access to clean water and sanitation for all, particularly in rural and marginalized areas of Kenya.